Promoting Authenticity in the ESP Classroom through Digital Learning Resources. - Boudinar, Somia; Debaghine, Mohamed Lamine (Academicus, 2026)
This study investigates the integration of digital learning resources to address the authenticity gap in English for Specific Purposes (ESP) instruction within the Computer Sciences Department at Setif 1 University, Algeria. Despite the growing recognition of authenticity as a pivotal factor in effective language learning, ESP classrooms in the Algerian higher education context continue to rely heavily on static, textbook-based materials that fail to replicate the linguistic demands of real-world professional environments. Employing a mixed-methods research design, this study combines quantitative data collected from a 20-item Likert-scale questionnaire administered to 45 Master 2 students across five sections with qualitative data gathered from semi-structured interviews with 5 ESP practitioners. Quantitative findings reveal that students perceive digital resources as moderately effective in enhancing authenticity, with an overall mean of 3.82 (SD = 0.74). Section-level analysis indicates that perceptions of the impact of digital resources on authenticity had the highest mean (M = 4.15), while challenges and limitations had the lowest (M = 3.31). Thematic analysis of teacher interviews uncovers four overarching themes: (1) the transformative potential of digital resources for authenticity, (2) infrastructural and pedagogical constraints, (3) the role of discipline-specificity in resource selection, and (4) professional development needs. The study concludes that while digital resources offer significant promise in bridging the authenticity gap, their effective integration requires systematic institutional support, targeted teacher training, and curriculum redesign informed by an analysis of authentic communicative needs.